KONSEPSI HUKUM NIKAH SIRRI DI INDONESIA : Upaya Sinkronisasi antara Living Laws dengan Positive Laws - M Faiz Kurnia Hadi (Indonesian Journal of Islamic Law, 2018)
This article discusses efforts to synchronize Islamic law as living law and positive law, focusing on nikah siri (unregistered marriage) in Indonesia as a socio-legal reality in the field of family law that faces legal disharmony, since nikah siri is considered valid under Islamic law as a law living within society, yet contradicts the Marriage Law and the Compilation of Islamic Law as positive law. This study aims to analyze: (1) the legal status of nikah siri in Indonesia according to living law and positive law, and (2) the possibility of synchronizing both legal systems. The research employs normative legal research with statutory, conceptual, and historical approaches, using library-based primary and secondary sources. The findings indicate that according to living law, which is normative and relatively static, nikah siri is legally valid despite potential illegality and harm, whereas according to positive law, it violates marriage registration and state administrative regulations, thus requiring legal sanctions. Furthermore, normative synchronization between living law and positive law faces a deadlock and is difficult to achieve; therefore, both should be repositioned as dynamic and empirical legal systems by shifting legal paradigms and approaches, so that Indonesian Islamic family law becomes more responsive to social realities and oriented toward the evolving welfare (maṣlaḥah) of the family.